"And it was not my fault..." Inequality, discrimination and gender-based violence against women in Puebla (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
In the context of capitalism in its neoliberal phase, the persistence of models on the duty of men and women, the precariousness of life in all its dimensions and an inefficient administration of justice, form the framework from which violence arises and feeds. feminicide, used as an excuse to discipline and teach women to be obedient. This context helps to explain, as the work shows, the case of feminicidal violence in the State of Puebla (Mexico), where the indices of poverty, human development, health, education, among others, show a setback that places it in the last places of national development. Added to this framework is the fight between and against organized crime, which not only involves the sale of drugs, but also includes human trafficking and prostitution. Other forms of violence against women have also grown in the entity, highlighting those suffered at home and with the partner. All these forms of violence culminate in feminicidal violence, which in recent years has grown significantly in the state.
Keywords: patriarchal capitalism; precariousness of life; feminicidal violence; Puebla (Mexico)